VD_FINDINFO Arrêt / 2018 / 227 vom 14. Februar 2018 - VD Tribunal cantonal (2018)
RENTE D'INVALIDITÉ, RÉVISIONPRESTATION D'ASSURANCE | 28 al. 2 LAI, 4 al. 1 LAI, 16 LPGA, 17 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA